ERA BARU KEMAS ULANG INFORMASI (KUI) SEBAGAI MEDIA PENDUKUNG PEMBELAJARAN SECARA DARING - Andi Saputra; Ernita Arif (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2021)
Information repackaging aims to overcome barriers to delivering information to users. The high frequency of use of learning management system applications and online meetings has caused various obstacles in the learning process, both in terms of learning models and the costs incurred to buy internet packages. This study aims to repack the lecture material using the assistance of the Youtube and Google Sites applications to support online learning activities. The method applied is applied research in a practical form. Repackaged information is lecture material. The packaging process begins with the selection of lecture materials. Lecture materials are arranged in the form of video tutorials which are divided into several sections. The results of media transfer are stored and published on Youtube. All lecture materials on Youtube are packaged on a website using Google Sites. This study concludes that the combination of Youtube and Google Sites can produce structured and attractive information in the form of an interactive website. Repackaging information using Youtube and Google Sites has changed the paradigm that has been developing, by eliminating dependence on physical media, such as CDs, DVDs, flash drives, and other storage media for storage and packaging media.